2013
DOI: 10.1016/j.celrep.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Localization of Cdx2 mRNA during the First Cell-Fate Decision in Early Mouse Development

Abstract: SummaryA longstanding question in mammalian development is whether the divisions that segregate pluripotent progenitor cells for the future embryo from cells that differentiate into extraembryonic structures are asymmetric in cell-fate instructions. The transcription factor Cdx2 plays a key role in the first cell-fate decision. Here, using live-embryo imaging, we show that localization of Cdx2 transcripts becomes asymmetric during development, preceding cell lineage segregation. Cdx2 transcripts preferentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 46 publications
2
57
0
Order By: Relevance
“…The apical localization of Cdx2 mRNA and its asymmetric inheritance by polar cells during asymmetric division is proposed to be involved in establishing TE-specific CDX2 expression (Jedrusik et al, 2010;Jedrusik et al, 2008;Skamagki et al, 2013). Precisely when CDX2 acts, however, remains unclear: some studies suggest that maternal CDX2 is required for proper cell cycle progression and cell survival (Jedrusik et al, 2015); however, a separate study has shown that there is no clear contribution of maternal CDX2 to lineage specification and that maternal CDX2 is dispensable for preimplantation development (Blij et al, 2012).…”
Section: Experimental Manipulations and Consequencesmentioning
confidence: 99%
“…The apical localization of Cdx2 mRNA and its asymmetric inheritance by polar cells during asymmetric division is proposed to be involved in establishing TE-specific CDX2 expression (Jedrusik et al, 2010;Jedrusik et al, 2008;Skamagki et al, 2013). Precisely when CDX2 acts, however, remains unclear: some studies suggest that maternal CDX2 is required for proper cell cycle progression and cell survival (Jedrusik et al, 2015); however, a separate study has shown that there is no clear contribution of maternal CDX2 to lineage specification and that maternal CDX2 is dispensable for preimplantation development (Blij et al, 2012).…”
Section: Experimental Manipulations and Consequencesmentioning
confidence: 99%
“…Thus, Hippo provides a candidate for the transduction of the mechanics of the cell, as represented in the cytoskeleton and adhesion system, to the transcriptional networks. Cell polarity and adhesion are also required for the asymmetric localisation and inheritance of Cdx2 mRNA at the 8-to 16-cell transition (Skamagki et al, 2013). Together, these two mechanisms will, over time, restrict Cdx2 expression to outside cells, where this transcription factor in turn can act to downregulate ICM-specific factors such as Oct4 (Niwa et al, 2005).…”
mentioning
confidence: 99%
“…At this time, the outer cells become committed to the TE lineage through upregulation of Cdx2 expression and concomitant downregulation of PrEnd-and Epi-associated genes. Additionally, an asymmetric distribution of Cdx2 mRNA at the 8-to 16-cell transition might contribute to elevating Cdx2 protein levels in outside cells and reducing them in inside cells (Skamagki et al, 2013). In the ICM, gene expression differences that are associated with emerging lineage restrictions can be detected by the 64-cell stage, when Nanog and Gata6 expression become mutually exclusive in individual cells (Plusa et al, 2008; Guo et al, 2010; Frankenberg et al, 2011).…”
mentioning
confidence: 99%
“…1), the idea that localized maternal determinants are used in embryonic axial patterning remains controversial. For example, some studies, but not others, find evidence for a maternal role of gene products proposed to be maternal determinants (Cdx2) (55,56) in cell-fate specification in the embryo (57)(58)(59). Nevertheless, a significant body of data suggests that zygotic regulators and cell-cell interactions determine axis polarity and patterning in mammals (e.g., refs.…”
Section: Evolution Of Inheritance May Not Necessarily Depend On Its Ementioning
confidence: 99%